Spatio-temporal variation of the suspended sediment concentration in the Pearl River Estuary observed by MODIS during 2003–2015 - Zhan, Weikang; Wu, Jie; Wei, Xing; Tang, Shilin; Zhan, Haigang (Continental shelf research, 2019)
Spatio-temporal variability of the suspended sediment concentration (SSC) in the Pearl River Estuary (PRE) is analyzed over 13 years (2003–2015) using MODIS-Aqua Level-1B data. A unique seasonal SSC variability was found. During the wet season, the SSC in the northwestern estuary (NWE) is high, which could reach up to 100 mg/L, while during the dry season it suffers from a markedly decrease. Over the southeastern estuary (SEE), however, the pattern is reversed. This seasonality is mainly affected by freshwater discharge, winds and water column stratification. During the wet season, freshwater discharge dominates the SSC in the NWE while stratification and water discharge control the SSC variation in the SEE. During the dry season, freshwater discharge also plays a more important role in changing the SSC in the NWE, while the combined effect of wind mixing and tidal mixing dominates the SSC in the SEE. The interannual variability of the SSC is revealed by an EOF analysis. The first mode is highly related to water discharge of the Pearl River, indicating that the interannual variability is mainly subject to the rainfall over the Pearl River basin. The long-term SSC trend is characterized by a general decrease across the entire estuary and proved to be closely related to human activity. The reduction rate of the SSC varies spatially and seasonally. Spatially, the northern West Shoal and upper eastern part of the PRE suffer from a much greater SSC decrease, while the rest of the estuary, especially the southern West Shoal, is relatively less influenced. Seasonally, the decreasing rate in the dry season (49.3%) is higher than that in the wet season (30.1%). •Seasonal variability of the SSC in the NWE and SEE are controlled by different factors.•Interannual variability of the SSC is subject to the freshwater discharge.•A significant decreasing trend of the SSC is detected, presumably due to dam constructions.•The reduction rate of the SSC in the dry season is higher than that in the wet season.